The effectiveness of tamagotchi purchase with purchase (PWP) promotion at Parkson Grand Sungei Wang Plaza, Kuala Lumpur / Anita Daud - Daud, Anita (1997)
This study is on the Tamagotchi Purchase With Purchase (PWP) promotion at Parkson Grand Sungei Wang Plaza, which started from June 20,1997 until stock last. Tamagotchi PWP promotion is one of Parkson important promotion to increase sales. In this study, we will look at the effectiveness of Tamagotchi PWP promotion at Parkson Grand Sungei Wang Plaza in order to attrack customers to spend more at Parkson . The study also look at the level of customers' awareness, their problems in understanding the promotion and the demographic profile. Two sources had been used to help the research meet the objectives that are questionnaire and also internal and external secondary data. 40 respondents involved in this study and only 6 of them who did not have any idea about Tamagotchi PWP promotion. From the findings, the study approve that this promotion is effective but not effective enough because some customers still have problems in understanding the promotion. At the end of this project paper, we will look at the recommendation for improving this kind of promotion in the future.